The Importance of Information and Communication Technologies in Education: Enhancing Learning in the Digital Age (Eurasian Journal of Learning and Academic Teaching, 2023)
This scientific article explores the significance of information and communication technologies (ICT) in education and their role in enhancing learning experiences in the digital age. The rapid advancement of technology has revolutionized the educational landscape, presenting new opportunities and challenges. By examining existing research and practices, this article highlights the transformative potential of ICT in education and its impact on student engagement, academic achievement, and the development of essential skills. Additionally, it discusses the challenges faced in integrating ICT effectively and offers recommendations for educators and policymakers to harness the full potential of these technologies for educational purposes.